Study of the pore solution and the microstructure of mineral additions blended cement pastes. (December 2017) - Cherif, R.; Hamami, A.A.; Aït-Mokhtar, A.; Meusnier, J-F
Abstract: In this paper, the influence of mineral additions on the microstructure and the chemical composition of the pore solution of cementitious materials is investigated. For this purpose, hardened cement pastes based on Portland cement CEM I are used. In order to study the influence of the cementitious materials composition on their microstructure and pore solution, a part of the cement is substituted by different mineral additions (limestone filler, fly ash, blast furnace slag and silica fumes). Experimental tests covered measurement of chloride diffusion coefficient by migration test and water and mercury porosimetry. Furthermore, pore solutions are extracted by pressing from cement pastes and analyzed by ionic chromatography. Results show that the substitution of cement by mineral addition modifies the total porosity and the pore sizes distribution of the blended cement pastes tested. Chemical analyses showed that all the tested pore solutions are mainly composed by sodium and potassium. A significant concentration of divalent ions, such as sulfates and calcium, is also noticed. The substitution of cement by mineral addition also significantly modifies the pore solution of cement pastes. In fact, a substitution of cement by 10% of silica fume decreases the alkalis concentrations and increases the sulfates and calcium ones. Thus, the divalent species (Ca 2+ and SO4 2- ) should be taken into account for the chloride diffusion modelling unlike the current models of the literature. Results of this chemical investigation could be used as initial and boundary conditions in the modeling of aggressive species transport through porous construction materials.